A Practical Framework for Evaluating Health Services Management Educational Program: The Application of The Mixed-Method Sequential Explanatory Design - Bazrafshan Azam; Haghdoost Aliakbar; Rezaie Habibalah; Beigzadeh Amin (Tabriz University of Medical Sciences, 2015)
Introduction:Health services managers are responsible for improving the efficiency and quality in delivering healthcare services. In this regard, Health Services Management (HSM) programs have been widely established to provide health providers with skilled, professional managers to address those needs. It is therefore important to ascertain the quality of these programs. The purpose of this study was to synthesize and develop a framework to evaluate the quality of the Health Services Management (HSM) program at Kerman University of Medical Sciences. Methods: This study followed a mixed-method sequential explanatory approach in which data were collected through a CIPP survey and semi-structured interviews. In phase 1, participants included 10 faculty members, 64 students and 90 alumni. In phase 2, in-depth semi-structured interviews and purposeful sampling were conducted with 27 participants to better understand their perceptions of the HSM program. All interviews were audio-taped and transcribed verbatim. NVivo N8 was used to analyze the qualitative data and extract the themes. Results: The data analysis revealed both positive and negative attitudes toward the HSM program. According to the CIPP survey, program objectives (74%), curriculum content (59.5%) and graduate skills (79%) were the major sources of dissatisfaction. However, most respondents (n=48) reported that the classes are well equipped and learning resources are well prepared (n=41). Most respondents (n=41) reported that the students are actively involved in classroom activities. The majority of respondents (n=43) pointed out that the instructors implemented appropriate teaching strategies. Qualitative analysis of interviews revealed that a regular community needs assessment, content revision and directing attention to graduate skills and expertise are the key solutions to improve the program's quality.Conclusion: This study revealed to what extent the HSM program objectives is being addressed. Learning barriers, further suggestions and modifications are provided to improve the quality of the program. It will serve as an initiative for future research on the systematic evaluation of the HSM program.